Women’s Labor Rights in Islam: Plight of Female Bonded Laborers in Brickkiln Industry of Kasur - Dr. Iram Rubab; Dr. Shahida Parveen (jihat-ul-islam, 2020)
Labor rights have been an area of keen interest across the globe. Islam, which is a widely practiced religion, provides a comprehensive framework regarding employer-employee relationships and hence, can be of value in this regard. Clear injunctions of Islam on the matter are further endorsed by the hadith of Holy Prophet (P.B.U.H). The present study is interested in exploring women’s labor rights in the Islamic tradition. It further investigates the plight of female bonded Laborers in the brickkiln industry of Kasur and compares it to Islamic injunctions. To execute the study plan, pure qualitative methods were used. Fifteen female Laborers from five brick kilns of Kasur were recruited as study participants. An in-depth interview guide was used as the tool for data collection, and the collected data were analyzed through narrative analysis technique. The study results revealed that in spite of Pakistan being a Muslim country, Islamic injunctions on labor rights are not being followed in the brickkiln industry. Forced Labor, debt bondage, wage discrimination, and double burden on female laborers were found to be quite prevalent. Amongst practices contrary to Islamic guidelines, it was also observed that female laborers have no control over any kind of financial resources and decision-making. Additionally, women were seen to be a prey of double marginality due intersectionality of their gender identity with their status as bonded laborers. Low nutritional levels, poor hygiene conditions, and absence of health facilities had made their lives more miserable. The fear of sexual assault was also quite pervasive, which had led many families to involve their underage girl children into labor at brick kilns. Girl children were even forced to work in illness due to fear of sexual assault at home. On the basis of study results, it is concluded that there is a dire need to incorporate Islamic injunctions in labor laws of Pakistan. In this regard, an awareness campaign about Islamic teachings concerning labor should be initiated. Most importantly, implementation mechanisms of already existing laws should be improved with an emphasis on improving the status of women laborers and freeing them from inhumane existence as bonded Laborers.